Vous êtes sur la page 1sur 3

𝑓(𝑥) = 𝑎𝑥 2 − 4𝑥 + 1

𝑔(𝑥) = 𝑓 ′ (𝑥) = 2𝑎𝑥 − 4 Las raíces son: (𝟒. 𝟑𝟓𝟒; 𝟎) y (𝟎. 𝟐𝟔𝟓; 𝟎)

𝑚 = 2𝑎 = 𝑎𝑟𝑐𝑡𝑔 60º

2𝑎 = √3 Vértice:

√3 𝑔(𝑥) = 𝑓 ′ (𝑥) = √3𝑥 − 4


𝑎=
2
0 = √3. 𝑥 − 4

4 = √3. 𝑥
Entonces:
4
√𝟑 𝟐 𝑥=
𝒇(𝒙) = 𝒙 − 𝟒𝒙 + 𝟏 √3
𝟐
4 √3
𝒈(𝒙) = √𝟑𝒙 − 𝟒 𝑥= .
√3 √3
4
𝑥 = √3
Raíces: 3
𝑥 ≅ 2.309
−𝑏 ± √𝑏 2 − 4𝑎𝑐
𝑥=
2𝑎 𝑓 ′ ′(𝑥) = √3

√3 𝑓 ′′ (𝑥) > 0 → 𝐸𝑠 𝑢𝑛 𝑚í𝑛𝑖𝑚𝑜


−(−4) ± √(−4)2 − 4 1
𝑥= 2
√3 √3 2
2 𝑓(𝑥) = 𝑥 − 4𝑥 + 1
2 2

4 ± √16 − 2√3 𝑓(𝑥) ≅ 0.866𝑥 2 − 4𝑥 + 1


𝑥=
√3 𝑓(2.309) ≅ 0.866. (2.309)2 − 4. (2.309) + 1
4 ± 3.541 𝑓(2.309) ≅ 4.617 − 9.236 + 1
𝑥≅
1.732
𝑓(2.309) ≅ −3.619
4 + 3.541
𝑥 1 ≅ ≅ 4.354
1.732
4 − 3.541 El vértice es: (𝟐. 𝟑𝟎𝟗, −𝟑. 𝟔𝟏𝟗)
𝑥 2 ≅ ≅ 0.265
1.732
5.-

Imagen = [1; 5]
Frecuencia = 1
Período = 2𝜋